A core microbiome in the hyphosphere of arbuscular mycorrhizal fungi has functional significance in organic phosphorus mineralization. Issue 2 (15th December 2022) - Wang, Letian; Zhang, Lin; George, Timothy S.; Feng, Gu
Summary: The mycorrhizal pathway is an important phosphorus (P) uptake pathway for more than two‐thirds of land plants. The arbuscular mycorrhizal (AM) fungi‐associated hyphosphere microbiome has been considered as the second genome of mycorrhizal P uptake pathway and functionality in mobilizing soil organic P (Po). However, whether there is a core microbiome in the hyphosphere and how this is implicated in mining soil Po are less understood. We established on‐site field trials located in humid, semiarid, and arid zones and a microcosm experiment in a glasshouse with specific AM fungi and varying soil types to answer the above questions. The hyphosphere microbiome of AM fungi enhanced soil phosphatase activity and promoted Po mineralization in all sites. Although the assemblage of hyphosphere microbiomes identified in three climate zones was mediated by environmental factors, we detected a core set in three sites and the subsequent microcosm experiment. The core members were co‐enriched in the hyphosphere and dominated by Alphaproteobacteria, Actinobacteria, and Gammaproteobacteria. Moreover, these core bacterial members aggregate into stable guilds that contributed to phosphatase activity. The core hyphosphere microbiome is taxonomically conserved and provides functions, with respect to the mineralization of Po, that AM fungi lack. Abstract : See also the Commentary on this article by Johnson & Marín, 238 : 461–463.